Symptom-specific gut microbial and metabolic profiles in ADHD reveal SCFA deficiency as a Key pathogenic mechanism - Xinyue Wang; Ning Wang; Teng Gao; Yunfan Zhang; Zhao Fu; Yilu Zhao; Yujingwen Huang; Xiangyu Zheng; Xuping Gao; Lin Lu; Li Yang (Gut Microbes)
Previous evidence links gut microbiota to attention-deficit/hyperactivity disorder (ADHD) through the gut-brain axis. However, the specific microbiota contributing to symptoms remain unclear. To characterize the gut microbial profile related to different symptoms and explore the mediation mechanism between microbiota alterations and the core ADHD symptoms, we conducted shotgun metagenomic sequencing and fecal metabolomics analysis on 94 ADHD patients and 94 age- and gender-matched controls. Microbial characteristics of three subgroups exhibiting different ADHD core symptom presentations were analyzed. We developed a metabolic model and conducted causal mediation analyses to examine how metabolites connect the microbiota to the symptoms. Fecal microbiota transplantation in mice was employed to validate the findings. The redundancy analysis identified ADHD symptoms as environmental gradients and explained the changes in beta diversity (F = 1.345, pFDR = 0.015). Greater gut microbial alterations were observed in combined presentations (ADHD-C). Several beneficial bacteria involved in short-chain fatty acid synthesis were found to be downregulated, with Lactobacillus sanfranciscensis notably linked to all three core symptoms (p.adj = 1.04E–13; p.adj = 5.07E–07; p.adj = 2.61E–05). Various taxa, functional pathways, and metabolites associated with specific ADHD symptom domains were identified. Imidazoleacetic acid partially mediated the effects between Lactobacillus sanfranciscensis and inattention (p = 0.012). In mice subjected to feces from ADHD patients with a low abundance of Lactobacillus sanfranciscensis, treatment with this strain greatly improved both hyperactivity (t = 2.665, p = 0.0237) and inattention (t = 2.389, p = 0.0380), while acetate supplementation only alleviated inattention (t = 2.362, p = 0.0398). Our findings suggest that different ADHD symptoms were related to common and different gut microbiota and metabolites. Fecal microbiota transplantation in mice validated the hypothesis that gut microbial composition affects ADHD symptoms through metabolic alterations. This study provides more insight into the mechanisms underlying metabolic disturbances in ADHD and elucidates the role of gut microbiota in these processes.